Enhanced Antibacterial Property of Pectin/Carboxymethyl Cellulose Films via Essential Oil Nanoemulsion and Silver Nanoparticles Integration - Tran, Quang Khanh; Dang, Le Phuong Linh; Nguyen, Thi Lan Anh; Nguyen, Thi Minh Thu; Do, Huy Hoang; Nguyen, Thi Son; Pham, Thanh Hien; Dang, Thanh Huyen; Mai, Duc Huynh; Le, Minh Dong; Nguyen, Duy Vuong; Ngo, Hong Anh Thu (Vietnam Journal of Science and Technology, 2025)
Pectin/Carboxymethyl cellulose (Pectin/CMC) films are biodegradable and edible materials with excellent film-forming properties but limited antibacterial properties. This study developed a novel essential oil nanoemulsion (EON) system by combining cinnamon essential oil with silver nanoparticles (AgNPs) to enhance the antibacterial properties of Pectin/CMC films for food preservation. Dynamic light scattering spectroscopy revealed that the cinnamon essential oil nanoemulsion in the Tween 80/Span 80 ratio at 0.75/0.25 achieved the smallest particle size of 78.32 nm and the most stable distribution. The EON/AgNP system exhibited robust antibacterial activity against E.coli over 7 days, highlighting its stability and efficacy in food preservation. Incorporating EON/AgNPs into Pectin/CMC films significantly enhanced their mechanical properties, increasing elongation at the break by 1.2 times while retaining tensile strength. Additionally, the films demonstrated improved sensory attributes, suggesting their potential as sustainable and efficient materials for future food packaging applications.